Can glucose‐lowering medications improve outcomes in non‐diabetic heart failure patients? A Bayesian network meta‐analysis - Yeong, Trevor; Mai, Aaron Shengting; Lim, Oliver Z.H.; Ng, Cheng Han; Chin, Yip Han; Tay, Phoebe; Lin, Chaoxing; Muthiah, Mark; Khoo, Chin Meng; Dalakoti, Mayank; Loh, Poay‐Huan; Chan, Mark; et al. (ESC Heart Failure, 2022)
Aims The cardioprotective effects of glucose‐lowering medications in diabetic patients with heart failure (HF) are well known. Several large randomized controlled trials (RCTs) have recently suggested that the cardioprotective effects of glucose‐lowering medications extend to HF patients regardless of diabetic status. The aim of this study was to conduct a Bayesian network meta‐analysis to evaluate the impact of various glucose‐lowering medications on the outcomes of non‐diabetic HF patients. Methods and results Medline and Embase were searched for RCTs investigating the use of glucose‐lowering medications in non‐diabetic HF patients in August 2021. Studies were included in accordance with the inclusion and exclusion criteria, and data were extracted with a pre‐defined datasheet. Primary outcomes include serum N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP) levels, left ventricular ejection fraction (LVEF), and maximal oxygen consumption (PVO2). A Bayesian network meta‐analysis was performed to compare the effectiveness of different classes of glucose‐lowering medications in improving HF outcomes. Risk‐of‐bias was assessed using Cochrane Risk‐of‐Bias tool 2.0 for randomized trials (ROB2). Seven RCTs involving 2897 patients were included. Sodium‐glucose transporter 2 inhibitor (SGLT2i) was the most favourable in lowering NT‐proBNP, with the significant reduction in NT‐proBNP when compared with glucagon‐like peptide‐1 receptor agonists (GLP1‐RA) [mean differences (MD): −229.59 pg/mL, 95%‐credible intervals (95%‐CrI): −238.31 to −220.91], metformin (MD: −237.15 pg/mL, 95%‐CrI: −256.19 to −218.14), and placebo (MD: −228.00 pg/mL, 95%‐CrI: −233.99 to −221.99). SGLT2i was more effective in improving LVEF for HF with reduced ejection fraction patients relative to GLP1‐RA (MD: 8.09%, 95%‐CrI: 6.30 to 9.88) and placebo (MD: 6.10%, 95%‐CrI: 4.37 to 7.84). SGLT2i and GLP1‐RA were more favourable to placebo in improving PVO2, with significant increase of PVO2 at a MD of 1.60 mL/kg/min (95%‐CrI: 0.63 to 2.57) and 0.86 mL/kg/min (95%‐CrI: 0.66 to 1.06), respectively. All three drugs had comparable safety profiles when compared with placebo. Conclusions This Bayesian network meta‐analysis demonstrated that SGLT2i, when compared with GLP1‐RA and metformin, was superior in improving LVEF in HF with reduced ejection fraction patients, as well as improving PVO2 and NT‐proBNP in non‐diabetic HF patients. Further large‐scale prospective studies are needed to confirm these preliminary findings.